2018
DOI: 10.1371/journal.pone.0201269
|View full text |Cite
|
Sign up to set email alerts
|

Variation in species diversity of deep-water megafauna assemblages in the Caribbean across depth and ecoregions

Abstract: Diversity patterns of the deep-sea megafauna in the Caribbean Basin and the Guiana ecoregion were analyzed in order to test the hypothesis of species richness variation as a function of depth and the hypothesis of non-differences between ecoregions by analyzing spatial patterns of five taxa and a merged assemblage. Collections of five taxa (corals, sea stars, sea urchins, sea lilies and gastropods) were obtained from seven oceanographic expeditions aboard the R/V Pillsbury at 310 stations between 60 and 7500 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…In addition, Barroso et al [6] reported four regions working with prosobranch Gastropods from Brazil down to 200 m depth. In agreement with these previous authors, Hernández-Âvila et al [15] also detected changes in species composition in relation to ecoregions and depth in the Caribbean.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, Barroso et al [6] reported four regions working with prosobranch Gastropods from Brazil down to 200 m depth. In agreement with these previous authors, Hernández-Âvila et al [15] also detected changes in species composition in relation to ecoregions and depth in the Caribbean.…”
Section: Discussionsupporting
confidence: 90%
“…In this work, species seem to be arranged by the characteristics of the water mass they inhabit, instead of by their geographic position as proposed by Linse et al [17], Barroso et al [6] and Hernández-Âvila et al [15; among others]. However, this is not applicable to Group A because of the lack of samples between 2000 and 3000 m depth at high latitudes.…”
Section: Discussionmentioning
confidence: 87%
“…Yet, despite recent technological developments, it is still difficult to sample this inaccessible environment due to strong currents, rough bottoms and high costs. Therefore, the deep sea is the least surveyed marine environment although having eminent species richness (Hernández-Ávila et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Large deep‐sea connectivity due to a lack of physical barriers in the Caribbean Sea area has recently been indicated (Hernández‐Ávila et al, ). For this reason, deep‐water species catalogued with Caribbean distribution, such as C. cubana, Etmopterus carteri Springer & Burgess 1985 , E. hillianus, E. robinsi, Centrophorus tessellatus Garman 1906 , M. owstoni, G. arae, G. antillensis, S. maculatus, S. torrei (Ebert et al, ), Somniosus sp.…”
Section: Discussionmentioning
confidence: 99%